A deterritorialized people: Toward constructing a theo‐diasporic space. Issue 3 (13th July 2021) - Yip, Man‐Hei
Abstract: This article argues that doing theology in the context of diaspora is inseparable from people's experiences in their materiality, contemporaneity, and heterogeneity. Diasporic experience, and in this case, the particularity of diasporic Hongkongers, not only helps broaden our horizons, but also provides new understanding of suffering and salvation, and casts light on the journey toward a theo‐diasporic space. In this space, theologians and church leaders are motivated to deepen theological reflection through the diasporic lens and destabilize epistemic structures that gives false hope and certainty. This ever‐expanding space inevitably deterritorializes our theological orientation and meanwhile, invites more vigorous discussion on diasporic subjectivity and its potentiality in the imaginative construction of theology.